Effect of different pruning operations on the plant growth, phytohormones and transcriptome profiles of the following spring tea shoots - Lu Lu; Wenwen Luo; Yanan Zheng; Jing Jin; Ruyi Liu; Yiqing Lv; Ying Ye; Jianhui Ye (Beverage Plant Research)
Pruning as an important agronomic operation plays a crucial role in the regulation of tea plant growth, development and dry tea quality. The effects of different pruning operations on the plant growth, phytohormones and transcriptome profiles of the following spring tea shoots were studied. Pruning-treated samples had generally increased median of the weight of 100 buds (two leaves and one bud, 15.5−20.5 g) and longer stem diameter (1.7−1.8 mm) whereas shorter shoot length (34.6−59.2 mm) at the stage of two leaves and one bud, compared with unpruned samples (14.0 g, 1.7 mm, 87.4 mm), among which heavy pruning in mid April and early May greatly accelerated the development of the following spring tea shoots. The levels of phytohormones (auxin, gibberellin 1, gibberellin 3, and trans-zeatin) were significantly increased in the spring buds of tea plants heavily pruned in May. The KEGG result indicated that the pathways of plant–pathogen interaction, plant hormone signal transduction and circadian rhythm were regulated by different pruning treatments. Heavy pruning in April or May, without autumn pruning was suitable for producing premium green tea due to the early development and the higher weight of 100 buds. This study provides scientific guidance to regulate the growth of the following spring tea shoots using plant pruning operations.